2007
DOI: 10.1080/01446190701225707
|View full text |Cite
|
Sign up to set email alerts
|

Ethical behaviour in the South African construction industry

Abstract: An opinion survey of South African architects, quantity surveyors, engineers and contractors regarding ethical behaviour within the construction industry reveals that South African contractors seem to possess a reputation for unethical conduct. The range of problems encountered includes collusion, bribery, negligence, fraud, dishonesty and unfair practices. While bribery in the form of payments and gifts is prevalent, fraud does not appear to be as serious a problem. Most construction professionals believe tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 14 publications
2
87
0
1
Order By: Relevance
“…Generally, the identified unethical practices in the construction industry include bribery, collusion, cover pricing and falsification of qualification documents, among others (Abdul- Rahman et al 2010;Azher, Selph & Maqsood 2011;Bowen et al 2007a;Shakantu 2006;Vee & Skitmore 2003). Table 1 shows a fuller list of the unethical practices identified in past literature.…”
Section: Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the identified unethical practices in the construction industry include bribery, collusion, cover pricing and falsification of qualification documents, among others (Abdul- Rahman et al 2010;Azher, Selph & Maqsood 2011;Bowen et al 2007a;Shakantu 2006;Vee & Skitmore 2003). Table 1 shows a fuller list of the unethical practices identified in past literature.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Of the three biggest economies in Africa, namely, Nigeria, Egypt and South Africa, Nigeria is the most corrupt. Nigeria is also more corrupt than neighbouring Ghana where Ameyaw et al (2017) and Bowen et al (2007a), respectively, found evidences of widespread corruption (see Figures 1 and 2). Whereas corruption in the country is not confined to any particular industry, studies have shown Nigeria has recently renewed efforts towards stamping out corruption in every area of its national life.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Truly ethics is not all about definition because it does not, set down the code of ethics nor establish how the code of ethics might be prepared. However, Bowen et al(2007) submitted that ethics is not just about recognizing an whether an objective is good but encompasses a careful thought in making viable choice or identifying if the choice is right or wrong. Within the construction industry context RICS (2000) posited ethics is a way of 'giving ones best to ensure that clients' interests are properly cared for, but in doing so the wider public interest is also recognized and respected!…”
Section: Definition Of Ethicsmentioning
confidence: 99%
“…An organization that constantly creates a negative ethical impact may encounter a diminishing market for its services and withdrawal of public approval. The potential for illegal and unethical behavior within the business to impact adversely the welfare of society is great (Bowen et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%